Aplikasi Formulasi Pakan Seimbang untuk Mendukung Peternakan Itik Petelur Ramah Lingkungan - Agung Prabowo; Aulia Evi Susanti (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Feed is a major factor in the business of laying ducks. Approximately 70% of the production is to feed. Therefore, to get optimum benefit, feed must be efficiently formulated. To efficient, feed must be balance, the content of feed nutrients must be in accordance with the needs of livestock, so the remaining nutrients out of feed is a minimum. In addition to efficient, balanced feed can also reduce environmental pollution. Waste produced from farm can be a source of contamination of water or wells, if there is no further waste management. One of the consequences of water pollution by livestock waste nitrogen levels are rising. To simplify and accelerate the balanced feed formulations required a software application. This paper aims to introduce balanced feed formulation based software. Application software consists of three main parts, namely database, data processing and results. Simulations conducted on laying ducks feed on the production period. Two types of feed used in this simulation, namely: regular feed (PB) and balanced feed (PS). Each type of feed is repeated five times. Simulation results with the feed formulation software application show significant difference between PB and PS feed. PS is better than PB. Application of balanced feed formulation can be used to support environmentally friendly farming laying ducks.